An Education for (Future) Health `Professionals and Literary Scholars: Audre Lorde's The Cancer Journals and Marisa Marchetto's Cancer Vixen - Cortés Vieco, Francisco José (Miscelánea: A Journal of English and American Studies, 2024)
Life-writing on breast cancer vindicates women’s health rights, but, as this article demonstrates, the autopathographies Cancer Journals (1980) by Audre Lordeand Cancer Vixen (2006) by Marisa Marchetto also have the potential to teach lessons to (future) health professionals and scholars in literary studies, so that they can, respectively, improve their interactions with patients and understand the therapeutic power of illness narratives to emotionally heal their authors and intended female readers. Lorde uses the weapon of anger both to criticize how cancer patients are dehumanized by the often-insensitive medical profession and to proudly assert her post-mastectomy identity as a one-breasted warrior.Meanwhile, Marchetto opts for humor to describe her eleven-month war against breast cancer and its associated complications: her lack of health insurance to treat her illness and her fear of losing her fiancé. Yet, as this article examines, Cancer Vixen shows the illuminating power of graphic medicine as a breakthrough narrative form, to mitigate the antagonism between doctors and cancer patients, while enhancing literary scholars’ and health professionals’ empathic understanding of patients’ personal stories of illness beyond clinical and hospitalencounters.
Keywords: breast cancer; graphic medicine; patient; health professionals; diaries